The correlation between the costs and clinical benefits of PD-1/PD-L1 inhibitors in malignant tumors: An evaluation based on ASCO and ESMO frameworks - Lin, Shen; Huang, Yaping; Dong, Liangliang; Li, Meiyue; Wang, Yahong; Gu, Dian; Wu, Wei; Nian, Dongni; Luo, Shaohong; Huang, Xiaoting; Xu, Xiongwei; Weng, Xiuhua (Frontiers in Pharmacology, 2023)
Background: Life expectancy for patients with malignant tumors has been significantly improved since the presence of the PD-1/PD-L1 inhibitors in 2014, but they impose heavy financial burdens for patients, the health care system and the nations. The objective of this study was to determine the survival benefits, toxicities, and monetary of PD-1/PD-L1 inhibitors and quantify their values. Methods: Randomized controlled trials (RCTs) of PD-1/PD-L1 inhibitors for malignant tumors were identified and clinical benefits were quantified by American Society of Clinical Oncology Value Framework (ASCO-VF) and European Society for Medical Oncology Magnitude of Clinical Benefit Scale (ESMO-MCBS). The drug price in Micromedex REDBOOK was used to estimate monthly incremental drug costs (IDCs) and the correlation between clinical benefits and IDCs of experimental and control groups in each RCT, and the agreement between two frameworks were calculated. Results: Up to Dec 2022, 52 RCTs were included in the quantitative synthesis. All the RCTs were evaluated by ASCO-VF, and 26 (50%) met the ASCO-VF “clinical meaningful value”. 49 of 52 RCTs were graded by ESMO-MCBS, and 30 (61.2%) RCTs achieved ESMO criteria of meaningful value. P-values of Spearman correlation analyses between monthly IDCs and ASCO-VF / ESMO-MCBS scores were 0.9695 and 0.3013, respectively. In addition, agreement between two framework thresholds was fair (κ=0.417, P = 0.00354). Conclusions: This study suggests that there might be no correlation between the cost and clinical benefit of PD-1/PD-L1 inhibitors in malignancy, and the same results were observed in subgroups stratified by drug or indication. The results should be a wake-up call for oncologists, pharmaceutical enterprises and policymakers, and meanwhile advocate the refining of ASCO and ESMO frameworks.